The awareness on gold investment among government servants in Johor Bahru, Malaysia / Aminah Najibah Muda and Nurul Hafizah Abdul Rauf - Muda, Aminah Najibah; Abdul Rauf, Nurul Hafizah (Faculty of Business and Management, 2013)
The present study aims to investigate the level of awareness on gold investment among government servants in Johor Bahru, Malaysia. This research studied on three dimensions that influence the awareness on gold investment which are types and values of gold, types of gold investment in Malaysia and portfolio diversification. The government servants from ages in the range of 18 up to 60 years old and they were all from different races, religions, education background, salary and job and occupation consisted as uniformed unit officer, teacher, financial analyst, politician and others. Data was collected through questionnaires distributed to 100 government servants in the area of Johor Bahru by using stratified sampling. Result of the present study shows that there was significant correlation relationship between factors of the awareness on gold investment and the awareness on gold investment. This study also used regression backward analysis in order to identify which factor is most significant to the awareness on gold investment among government servants in Johor Bahru and the result was portfolio diversification. This study is said to be beneficial to any legal institution that offers gold investment channel as well as Malaysian government to promote the main influenced factor in order to gain awareness towards gold investment among government servants. Recommendations for future research also have been discussed.